(untitled) (Global Journal of Human-Social Science, 2023)
The events taking place in modern Ukraine actualize military issues The future of Ukraine as a sovereign state depends on an objective assessment of the situation and the adequacy of its perception The role of sociology as a science that focuses on understanding social reality in our case - war is essential in this aspect Its consequences are felt not only for Ukraine but also for the international community